Aspergillus flavus infection and aflatoxin contamination of preharvest maize in the Republic of Benin - Setamou, M.; Cardwell, K.; Schulthess, F.; Hell, K. (Scientific Societies, 1997)
Eighty and sixty maize fields were sampled in 1994 and 1995, respectively, to monitor Aspergillus infection and aflatoxin contamination of preharvest maize in Benin. Three Aspergillus species were isolated from different agroecological zones, with A. flavus being the most prevalent. The countrywide mean percentage of kernel infection was about 20% in both years. Aflatoxin was extracted from maize in at least 30% of the fields sampled. Toxin concentrations exhibited a distinct zonal variation, with relatively high levels in the Guinea Savanna. There was a trend toward higher rate of aflatoxin accumulation per percentage A. flavus infection from the south to the north. Damage by the ear borer, Mussidia nigrivenella, increased aflatoxin accumulation in maize. Hence, the geographic pattern observed in the occurrence of A. flavus and aflatoxin may be related to the incidence of M. nigrivenella.